Epigenetic Regulation of T Cell Memory: Recalling Therapeutic Implications. Issue 1 (January 2020) - Tough, David F.; Rioja, Inma; Modis, Louise K.; Prinjha, Rab K.
Abstract : Memory T cells possess functional differences from naïve T cells that powerfully contribute to the efficiency of secondary immune responses. These abilities are imprinted during the primary response, linked to the acquisition of novel patterns of gene expression. Underlying this are alterations at the chromatin level (epigenetic modifications) that regulate constitutive and inducible gene transcription. T cell epigenetic memory can persist long-term, contributing to long-lasting immunity after infection or vaccination. However, acquired epigenetic states can also hinder effective tumor immunity or contribute to autoimmunity. The growing understanding of epigenetic gene regulation as it relates to both the stability and malleability of T cell memory may offer the potential to selectively modify T cell memory in disease by targeting epigenetic mechanisms. Highlights: Precise control of gene expression is achieved by epigenetic mechanisms involving covalent modifications to DNA and histones that alter chromatin structure. T cell activation and differentiation into effector cells is accompanied by widespread epigenetic modifications and marked changes in gene expression. Memory T cells retain a long-term epigenetic imprint that confers constitutive and inducible gene expression associated with a rapid recall response capacity. Exhausted T cells generated in response to chronic antigen exposure are functionally defective and epigenetically distinct from both effector and memory T cells. Blocking inhibitory receptors on Tex cells transiently restores function but has little effect on the epigenetic memory of these cells. Epigenetic mediators have been identified that can modulate T cell differentiation into effector, memory, and exhausted cells.